Attitudes towards learning disabilities and ADHD syndrom in students qualified for various sociometric status groups attending vocational schools - Monika Mirosława Wypych (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Attention Deficit Hyperactivity Disorder (ADHD) is a very interesting issue as long as such professionals as physicians, educators, psychologists and sociologists are concerned. Taking into account the disorders that are connected with this complex syndrome being usually observed in childhood and adolescence, they actually co-exist with learning difficulties. Besides the typical neurological and psychosocial dysfunctions resulting from these disorders, affecting both the child and his/her close surroundings, one should not forget about the role played by school which sometimes leads to other problems. Attitudes towards people with learning disabilities and ADHD may be different in various types of educational settings. My comprehensive study reveals that the socio-metric status of a student of a vocational school has an effect on his/her attitude towards these phenomena and people with such disorders. It is supposed to be true that sometimes more favorable attitudes towards learning disabilities and ADHD are observed for the students who tend to be disliked or rejected by others in the classroom. Based on the results of my research, it was found that the disliked students in the class showed more positive attitudes towards learning difficulties and ADHD syndrome than their peers who were liked by others in regard to two out of four variables. Regarding factor 2 of Attitudes towards Learning Difficulties and ADHD Syndrome Rating Scale by P. Gindrich, a reverse tendency was found because the students of "the liked group" showed far more positive attitudes in regard to this factor. Furthermore, the analysis of socio-metric status revealed that the overall level of social/peer acceptance (assessed with the total of positive responses received from other classmates) had an impact on the attitudes of youth attending vocational schools.